2011
DOI: 10.1165/rcmb.2010-0125oc
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Matrix Metalloproteinases 2 and 9 Regulate Activation of CD4+and CD8+T cells

Abstract: We reported that inhibiting matrix metalloproteinases (MMP), known to remodel the extracellular matrix, also down-regulated antigen-specific T-cell responses. However, the direct role of MMP2 and MMP9 in regulating intracellular function in T cells is unknown. Markers of cellular activation and cytokine profiles were examined in anti-CD3-stimulated wild-type C57BL/6 mouse-derived CD4(+) or CD8(+) T cells, or MMP2- or MMP9-deficient (-/-) mice. MMP-sufficient T cells were also treated with SB-3CT, a highly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 43 publications
2
46
0
2
Order By: Relevance
“…In the present study, the differential analysis of naive, effector memory and central memory T cells also revealed that IL-22 has no general influence on the development of memory and central memory T cells after infection with Mtb . Reduced numbers of naive CD4 + T cells at early stages of infection day may be explained by slightly reduced expression of the IL-22-dependent chemokines MMP-1 and CXCL-10 in IL-22 −/− mice, which are involved in activation and recruitment of T cells [56], [57], [70], [71] (data not shown). In line with the rather unaffected development of memory and central memory T cells in Mtb -infected IL-22 −/− mice the differentiation of IFNγ + IL-17A + T cells as well as of TH1 and TH17 cells was also fairly induced in the absence of IL-22.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the differential analysis of naive, effector memory and central memory T cells also revealed that IL-22 has no general influence on the development of memory and central memory T cells after infection with Mtb . Reduced numbers of naive CD4 + T cells at early stages of infection day may be explained by slightly reduced expression of the IL-22-dependent chemokines MMP-1 and CXCL-10 in IL-22 −/− mice, which are involved in activation and recruitment of T cells [56], [57], [70], [71] (data not shown). In line with the rather unaffected development of memory and central memory T cells in Mtb -infected IL-22 −/− mice the differentiation of IFNγ + IL-17A + T cells as well as of TH1 and TH17 cells was also fairly induced in the absence of IL-22.…”
Section: Discussionmentioning
confidence: 95%
“…As noted, these include MMP‐9, with increased mRNA levels in the lungs of mice after irradiation, changes that were significantly blunted by fTyS. Because T‐cell activation contributes to the elaboration of radiation pneumonitis (52), an important role for MMP‐9 in the pathogenesis of RILI is suggested by evidence that MMP‐9 regulates lung injury mediated by T cells (53). Separately, similar changes were observed with respect to both S100a8 and S100a9, also known as myeloid‐related proteins 8 and 14 (MRP8 and MRP14), respectively, which are increased in a variety of inflammatory states and contribute to EC barrier disruption and apoptosis (54).…”
Section: Discussionmentioning
confidence: 96%
“…After chemotaxis, MMPs also regulate inflammatory cell function. Gelatinase inhibition depresses lymphocyte proliferation in vitro and in vivo in experimental lung disease (12). MMP-8 and -9 promote neutrophil survival (23,58).…”
Section: Mechanisms Of Mmp Action In Kidney Diseasementioning
confidence: 99%